Aplikasi Mobile Pendaftaran Pasien Klinik Berbasis Algoritma Multilevel Queue Dan FIFO Untuk Meningkatkan Layanan Antrian - Priambudi, Abiyoga; Wijaya, Yunan Fauzi; Darusalam, Ucuk (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2024)
In this continuously evolving era of technology, the use of smartphone has become commonplace, including in the healthcare sector. However, there are still several issues such as long queues, uncertain appointment scheduling, and unexpected waiting times in the case of health care service such as in a hospital. Therefor, the aim of this research is to address these problems by developing a mobile application that utilizes multilevel queue and FIFO algorithms. The methods used in this research include data collection through questionnaires and documentation. A specific clinic is the subject of this study, involving both patients and clinic staff. The expected outcome is to enhance patient satisfaction through more efficient and expedited registration and queue processes. The result can enhance patient satisfaction because the registration and queueing process becomes faster and more efficient.